Analisis Strategi Pengembangan dan Perencanaan Manajemen Sumber Daya Manusia di Kantor Dinas Pariwisata Kabupaten Tana Toraja - Kezia Linmard; Dina Ramba; Adriana Madya Marampa (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the strategies for human resource (HR) development and planning at the Tourism Office of Tana Toraja in supporting organizational performance improvement and public service quality in the tourism sector. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and document analysis involving structural officials and relevant staff. The results indicate that HR development strategies are implemented through employee potential mapping, technical and managerial training programs, and periodic performance mentoring. Meanwhile, HR planning is conducted through employee inventory, job needs analysis, and competency-based development planning aligned with organizational duties and functions. The evaluation of the programs shows an improvement in employee competencies, particularly in tourism services and destination management. However, the implementation still faces several challenges, including budget limitations, a shortage of qualified experts, and the suboptimal application of competency-based HR planning systems. The study recommends enhancing the quality and sustainability of training programs, strengthening competency-based recruitment systems, and integrating HR planning with regional tourism development strategies to ensure sustainable organizational performance and service excellence.